Troubling Habits: Nuns, Faith, and Fashion in 1960s Popular Culture - Lankewish, Vincent A. (Religion and the arts, 2020)
Against the backdrop of a new progressivism ushered into existence in the Roman Catholic Church by the Vatican II Council initiated by Pope John XXIII in 1962 and concluded by Pope Paul VI in 1965, this essay examines nuns’ resistance to and eventual adoption of new professional garb as a site of sometimes contentious debates about the changing roles of women ecclesiastics. Within the context of passionate and, at times, violent fights for civil and women’s rights and of protests against U.S. involvement in Vietnam, two popular films from this decade— The Trouble with Angels (1966) and its sequel, Where Angels Go, Trouble Follows (1968)—stage a competition between tradition and innovation in both theological and sartorial arenas. Ultimately, the nuns in these films follow a calling to become public advocates for a more humane and charitable world.